Peningkatan Kualitas Alpokat Selama Masa Penyimpanan Menggunakan Edible Coating dari Pati Kulit Singkong - Mutiara Riyanto Putri; Noviar Harun; Yelmira Zalfiatri (JURNAL AGROINDUSTRI HALAL, 2025)
The purpose of this research was to get the best starch concentration of cassava peel in the manufacture and the effect of edible coating on the quality of avocado. This research was conducted experimentally by using a completely randomized design with four treatments and four replications. The treatments in this research were P1 (concentration of starch cassava peel 1%), P2 (concentration of starch cassava peel 2%), P3 (concentration of starch cassava peel 3%), and P4 (concentration of starch cassava peel 4%) in edible coating of starch cassava peel formulation which applied to the avocado and stored for 15 days. Data obtained were statistically analyzed using analysis of variance (ANOVA) and continued with Duncan’s new multiple range test (DNMRT) at a 5% level. The parameters observed in avocado were weight loss, total dissolved solid, hardness and hedonic test of color and aroma. The best treatment in this research was P4 (concentration of starch cassava peel 4%). This treatment can maintain fruit quality for 15 days of storage so that avocados have a weight loss of 29.13%, total dissolved solids 1.43°Brix, hardness 8.10 kg/f, and hedonic tests for color 3.15 (somewhat favored) and aroma 3.12 (somewhat favored).